2008
DOI: 10.1128/mcb.00127-08
|View full text |Cite
|
Sign up to set email alerts
|

Visual Analysis of the Yeast 5S rRNA Gene Transcriptome: Regulation and Role of La Protein

Abstract: 5S rRNA genes from Saccharomyces cerevisiae were examined by Miller chromatin spreading, representing the first quantitative analysis of RNA polymerase III genes in situ by electron microscopy. These very short genes, ϳ132 nucleotides (nt), were engaged by one to three RNA polymerases. Analysis in different growth conditions and in strains with a fourfold range in gene copy number revealed regulation at two levels: number of active genes and polymerase loading per gene. Repressive growth conditions (presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 72 publications
(110 reference statements)
6
45
0
Order By: Relevance
“…Other in vitro studies show no role for La protein in RNAPIII transcription (Pannone et al 1998;Weser et al 2000;Hu et al 2003). Recent work from French et al (2008) might reconcile both hypotheses. Using EM to visualize RNAPIII on the yeast 5S rRNA, a higher average RNAPIII density was detected in a strain deleted for the yeast La protein, and ChIP assays demonstrated an association of La protein with the 5S gene, apparently mediated by the nascent RNA.…”
Section: Does Rnapiii Need Auxiliary Factors To Terminate?mentioning
confidence: 95%
See 1 more Smart Citation
“…Other in vitro studies show no role for La protein in RNAPIII transcription (Pannone et al 1998;Weser et al 2000;Hu et al 2003). Recent work from French et al (2008) might reconcile both hypotheses. Using EM to visualize RNAPIII on the yeast 5S rRNA, a higher average RNAPIII density was detected in a strain deleted for the yeast La protein, and ChIP assays demonstrated an association of La protein with the 5S gene, apparently mediated by the nascent RNA.…”
Section: Does Rnapiii Need Auxiliary Factors To Terminate?mentioning
confidence: 95%
“…Using EM to visualize RNAPIII on the yeast 5S rRNA, a higher average RNAPIII density was detected in a strain deleted for the yeast La protein, and ChIP assays demonstrated an association of La protein with the 5S gene, apparently mediated by the nascent RNA. French et al (2008) showed that La has no effect on the rate of synthesis and size of 5S rRNA but proposed that the extra RNAPIII visualized at the 5S gene in the yeast laD strain reflects a defect in RNAPIII release.…”
Section: Does Rnapiii Need Auxiliary Factors To Terminate?mentioning
confidence: 99%
“…The reason for positive ChIP signal in the regions of rDNA that are devoid of Pol I remains unknown. However, it is known that Pol II transcripts originate from the NTS regions of the rDNA, and Pol III is active at the 5S rRNA genes (27,28). Thus, this signal may result from association of these factors with the other polymerases that are clearly active in the spacers between 35S rRNA genes.…”
Section: Subunits Of Paf1cmentioning
confidence: 99%
“…On the genes with a hairpin ≥ 5 nt upstream of the T-tract, RNAP III would have to back up as part of termination but, as shown by the new data, without RNA 3′ end retraction. 13 The elongation rate for RNAP III on yeast 5S rRNA genes has been calculated to be 60-75 nt/s with an occupancy of 2-3 RNAP III molecules per 5S gene and a reinitiation interval of 1.2 s. 94 Calculations based on tRNA levels in yeast estimate the rate of RNA production, i.e., termination, at 2-4 transcripts/gene/s 95 (or a time between two successive terminating RNAP III molecules equal to 250-500 ms). To put it another way, an RNAP III molecule involved in tRNA production in fast growing yeast cells has only 0.25-0.5 s to terminate as it approaches the terminator.…”
mentioning
confidence: 99%
“…As noted, yeast 5S rRNA genes of 132 bp contains 2-3 elongating RNAP III molecules. 94 Many tRNA genes contain introns and are as long as this, and dimeric tRNA genes are significantly longer, apparently loaded with successive RNAP III.…”
mentioning
confidence: 99%